Insights Into Patient Variability During Ivacaftor-Lumacaftor Therapy in Cystic Fibrosis - Hanafin, Patrick O.; Sermet-Gaudelus, Isabelle; Griese, Matthias; Kappler, Matthias; Ellemunter, Helmut; Schwarz, Carsten; Wilson, John; Tan, Marsha; Velkov, Tony; Rao, Gauri G.; Schneider-Futschik, Elena K. (Frontiers in Pharmacology, 2021)
Background: The advent of cystic fibrosis transmembrane conductance regulator protein (CFTR) modulators like ivacaftor have revolutionised the treatment of cystic fibrosis (CF). However, due to the plethora of variances in disease manifestations in CF, there are inherent challenges in unified responses under CFTR modulator treatment arising from variability in patient outcomes. The pharmacokinetic (PK) data available for ivacaftor-lumacaftor cystic fibrosis (CF) transmembrane conductance regulator (CFTR) modulator drug combination is limited. Methods: This study aimed to characterize their PK profile in 60 patients from 5 different CF centres. Secondary objectives were to identify (1) patient characteristics and (2) the interactions between ivacaftor-lumacaftor responsible for interindividual variability (IIV). Results: Peak plasma concentrations (Cmax) of ivacaftor - lumacaftor were >10 fold lower than expected compared to label information. The one-way ANOVA indicated that the patient site had an effect on Cmax values of ivacaftor metabolites M1, M6, and lumacaftor (p<0.001, p<0.001, and p<0.001, respectively). The Spearman’s rho test indicated that patient weight and age have an effect on the Cmax of lumacaftor (p=0.003 and p<0.001, respectively) and ivacaftor metabolite M1 (p=0.020 and p<0.001, respectively). Age (p<0.001) was found to effect on Cmax of ivacaftor M6 and on Tmax of ivacaftor M1 (p=0.026). A large impact of patient characteristics on the IIV of PK parameters Cmax and Tmax, was observed among the CF patients. Conclusion: Understanding the many sources of variability can help reduce this individual patient variability and ensure consistent patient outcomes.